A Comparative Study of the Motor Proficiency of Preschool Children in Greece and Germany through the Application of the Battery “Karlsruher Motorik-Screening” (KMS 3-6) - Papadopoulos, Δημήτριος; Kambas, Αντώνης; Christoforidis, Χρήστος; Fatouros, Ιωάννης; Taxildaris, Κυριάκος (Inquiries in Physical Education and Sport, 2007)
The purpose of the study was to compare the motor proficiency of 65 preschool children from Greece and 54 of the same age from Germany. The motor proficiency of the children was evaluated by using the “Karlsruher Motorik-Screening” (KMS 3-6) test battery, consisting of the following four items: one foot standing, lateral springs, long jump from the stance position and the test ‘’stand and reach’’. Multivariate analysis of variance (MANOVA) revealed that, compared to their German mates, Greek children: 1) exhibited significantly lower scores in lateral springs and long jump from the stance position, 2) exhibited significantly higher scores in one foot standing Balance and 3) were similar in the test ‘’stand and reach’’. Furthermore, there was no ‘’sex’’ influence on the children’s performance at any age, except of the performance in long jump from the stance position and that one in lateral springs at the age of four years, in which boys exhibited better performance. On the contrary, the performance in the test battery differentiated among the three aged groups, with the exception of the ‘’stand and reach’’ test, in which the differences were no significant. In conclusion, the level of motor proficiency in Greek children appeared to be lower, compared to that of the German children, which reveals a necessity for more effective development of the motor proficiency in the Greek nursery school.